PENGELOLAAN LUBUK LARANGAN DI SUNGAI KAMPAR - Mohd. Yunus (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
Various challenges have threatened the existence and sustainability of the lubuk larangan. Therefore, joint efforts and actions are needed to strengthen and ensure the sustainability of the lubuk larangan. Before the joint action can be realized, a study is needed that describes the current conditions of the management of the lubuk larangan. The purpose of this study is to describe and analyze the management of the lubuk larangan in the Kampar river. This study was carried out on October 2019 until January 2020. The location of the study was in Riau Province, namely in Kampar Regency and in West Sumatra Province, namely in Pasaman and Lima Puluh Kota Regency. Data collected includes primary data and secondary data. The analytical method used is descriptive analysis. The history of the formation of a lubuk larangan in general stems from the existence of a need in society to address interests. Most of the lubuk larangan bases located in West Sumatra are familiar with the zoning system, namely the distribution of prohibition bases into several zones according to their functions, including the core zone, buffer zone and utilization zone. Equipment used to catch fish is very simple such as fishing rods, nets, traps, shooting, and so forth. Lubuk larangan crops can then be sold back to the local community or migrants. Lubuk larangan maintenance activities that have been carried out include activities initiated by the relevant institution or initiated by the community itself. Lubuk larangan is supervised by a group formed through village / nagari deliberations, namely the community watch group (POKMASWAS) lubuk larangan.